Visceral hypersensitivity in female but not in male serotonin transporter knockout rats. Issue 6 (17th April 2013) - Galligan, J. J.; Patel, B. A.; Schneider, S. P.; Wang, H.; Zhao, H.; Novotny, M.; Bian, X.; Kabeer, R.; Fried, D.; Swain, G. M.
Abstract Background Visceral hypersensitivity occurs in irritable bowel syndrome (IBS), particularly in women. Serotonin signaling, including reduced serotonin transporter (SERT) expression, may be disrupted in IBS patients. We studied SERT gene knockout (KO) rats to determine if they exhibited sex‐related alterations in visceral sensitivity. Methods We measured serotonin in the colonic mucosa using HPLC and amperometric microelectrode techniques. Visceral sensitivity was assessed using the electromyographic visceromotor response (VMR) in response to colorectal balloon distention (CRD). We studied the electrophysiologic properties of colon projecting sensory neurons in vitro using whole‐cell recordings. Key Results Mucosal serotonin levels were not different among male and female WT and SERT KO rats. Serotonin oxidation currents in vitro were larger (P < 0.05) in tissues from male and female SERT KO compared with WT rats. Oxidation currents in male and female WT, but not SERT KO, rats were increased (P < 0.05) by the SERT inhibitor fluoxetine (1 μmol L−1). The VMR to CRD was increased in female but not in male SERT KO rats (P < 0.05); this response varied with the estrous cycle. Colon projecting sensory neurons from female SERT KO rats fired more action potentials compared with neurons from female WT rats. There were no differences in action potential firing in neurons from male WT and SERT KO rats. Conclusions & Inferences Increased colonic extracellular serotonin in female SERT KO rats is associated with visceral hypersensitivity and hyperexcitability of colon projecting sensory neurons. The SERT KO rat is a model for studying interactions between serotonin, sex and visceral sensation.